A Differentiated Instruction-Oriented Physics e-Module: Development and Its Impact on Conceptual Understanding - Lubis, Rajo Hasim; Br Manurung, Siska Yulianti; Tampubolon , Togi; Wahyuni , Ida; Panggabean, Deo Demonta; Sinaga , Johana Theresia (Universitas Negeri Semarang, 2025)
Based on observations conducted at a senior high school in Medan, the previously utilized e-module proved to be underexploited, primarily due to its limited format, comprising static text, images, and video links, which failed to accommodate the varied learning preferences of students. This misalignment contributed to low impact on learning outcomes, particularly in Work and Energy. The present study sought to design a differentiated-instruction-based e-module that is pedagogically valid, practically feasible, and demonstrably effective in fostering conceptual understanding. Employing a Research and Development (R&D) framework grounded in the 4-D model (Define, Design, Develop, Disseminate), data were gathered through expert validation instruments, response questionnaires, and achievement tests. Subject matter experts rated the module highly valid, while media specialists deemed it moderately valid. Teacher feedback and field trials affirmed its practical applicability. N-gain analysis of pretest–posttest results indicated substantial learning gains. The findings underscore the module’s efficacy and pedagogical value in delivering structured, engaging, and accessible instruction.